Pemanfaatan Lactobacillus plantarum 1 RN2-53 dalam Pembuatan Minuman Probiotik Berbasis Sari Buah Melon dengan Variasi Penambahan Sukrosa - Yusmarini Yusmarini; Vonny Setiares Johan; Shanti Fitriani; Emma Riftyan; Olo Marasi Siagian (Jurnal Teknologi dan Industri Pertanian Indonesia, 2021)
Lactic acid bacteria which have the potential as probiotic agents are often used in the manufacture of functional food products and one of them is fermented drink. The research objective was to utilize isolate of Lactobacillus plantarum 1 RN2-53 in the manufacture of melon juice-based fermented drinks and to acquire the best concentration of sucrose addition for the quality of fermented drinks. The study used a randomized complete design which variations in the addition of sucrose treatment, namely without the addition of sucrose as a control and the addition of sucrose 2, 4, 6, and 8%, respectively. Each treatment was repeated three times. The data obtained were analyzed statistically using analysis of variance with SPSS version 26 software. The results showed that variations in the addition of sucrose had a significant effect on the total lactic acid, total solids, taste and overall hedonic test, but had no significant effect on the pH value, total lactic acid bacteria, color and aroma of fermented drinks. The addition of 4% sucrose resulted in a better fermented drink with a pH value of 3.74; total lactic acid was 0.510%; total lactic acid bacteria was 8.477 log CFU/ml and total solids was 5.99%. Descriptively fermented drinks have a greenish white color, lack a distinctive fermented aroma, taste of sweet and sour, overall somewhat favored by the panelists.